The Impact of Service Quality on Business Commitment in Contract Manufacturing Services: An Exploratory Study of F&B Industry in Malaysia - Zulkefli Abdul Rahim; Boo-HoVoon; Rasidah Mahdi (International Journal of Business and Society, 2020)
Business environment is highly competitive for food & beverage(F&B)industry due to the low entry barrier. In order to improve their financial performances, F&B manufacturers opt to offer contract manufacturing services (CMS).There is a formal relationship established between the service provider and the buyer. However, the impact of service quality on retaining the business relationship particularly has not been empirically investigated. To fill this gap, this study explores the determinants of contract manufacturing service quality (CMSQ) and the interrelationship between CMSQ, customer satisfaction and loyalty of the F&B CMSs’ customers in Malaysia. Four focus group interviews (28 participants) were held in this study and they comprised 12 contract manufacturers and 16 business customers. Three new dimensions were discovered from the focus group interviews; product development capability, Halal certification and outcome quality in addition to the SERVQUAL dimensions. Relevantinformation via structured questionnaires were collected via online survey and drop-off method. 146 usable questionnaires were analysed using partial least squares. The results indicate that CMSQ consists of eight dimensions namely empathy, assurance, reliability, responsiveness, tangibles, outcome quality, Halal certification and product development capability. The Empathy dimension is the most important dimension influencing customers’ decision to stay with the contract manufacturers.CMSQ was found to have a small effect size on loyalty while customer satisfaction largely influenced loyalty. The result implies that CMSQ is a complement in the formation of customer loyalty while customer satisfaction is a significant predictor of behavioural intention.The findings also provide empirical evidence that the contextual specific service quality is essential particularly for contract manufacturing in F&B.